Comparison of Acceptable Noise Level Generated Using Different Transducers and Response Modes. (26th June 2018) - Xia, Liang; He, Jingchun; Sun, Yuanyuan; Chen, Yi; Luo, Qiong; Shi, Haibo; Feng, Yanmei; Yin, Shankai
Abstract : The acceptable noise level (ANL) was defined by subtracting the background noise level (BNL) from the most comfortable listening level (MCL) (ANL = MCL − BNL). This study compared the ANL obtained through different methods in 20 Chinese subjects with normal hearing. ANL was tested with Mandarin speech materials using a loudspeaker or earphones, with each subject tested by himself or by the audiologist. The presentation and response modes were as follows: (1) loudspeaker with self-adjusted noise levels using audiometer controls (LS method); (2) loudspeaker with the subject signaling the audiologist to adjust speech and noise levels (LA method); (3) earphones with self-adjusted noise levels using audiometer controls (ES method); and (4) earphones with the subject signaling the audiologist to adjust speech and noise levels (EA method). ANL was calculated from three measurements with each method. There was no significant difference in the ANL obtained through different presentation modes or response modes sound. The correlations between ANL, MCL, and BNL obtained from each two methods were significant. In conclusion, the ANL in normal-hearing Mandarin listeners may not be affected by presentation modes such as a loudspeaker or earphones nor is it affected by self-adjusted or audiologist-adjusted response modes. Earphone audiometry is as reliable as sound field audiometry and provides an easy and convenient way to measure ANL.